2008
DOI: 10.1194/jlr.r800008-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Thematic Review Series: Sphingolipids. Cross-talk at the crossroads of sphingosine-1-phosphate, growth factors, and cytokine signaling*

Abstract: Sphingosine-1-phosphate (S1P) is a bioactive sphingolipid that mediates a wide array of biologic effects through its interaction with a family of five G protein-coupled receptors. Cytokines and growth factors interact with this signaling pathway in a variety of ways, including both activation and regulation of the expression of the enzymes that regulate synthesis and degradation of S1P. Not only do many growth factors and cytokines stimulate S1P production, leading to transactivation of S1P receptors, ligation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 66 publications
(87 reference statements)
2
70
0
Order By: Relevance
“…It was shown that production of S1P is stimulated by several growth factors during activation of proliferation (Lebman & Spiegel 2008. Clinical data confirmed the importance of sphingolipid signalling in human breast carcinomas (Ruckhäberle et al 2008.…”
Section: Figuresupporting
confidence: 61%
See 1 more Smart Citation
“…It was shown that production of S1P is stimulated by several growth factors during activation of proliferation (Lebman & Spiegel 2008. Clinical data confirmed the importance of sphingolipid signalling in human breast carcinomas (Ruckhäberle et al 2008.…”
Section: Figuresupporting
confidence: 61%
“…Notably, sphingolipid metabolism is activated during normal cell growth and division not only to provide a basic supply of structural and functional metabolites but also to serve as second messengers (Lebman & Spiegel 2008, Aoyagi et al 2012. In this review, we analysed recent knowledge gained at the crossroads of sphingolipid and oestrogen signalling pathways in breast cancer cells (BCC).…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39][40] SphK1 can be activated by several mediators, and S1P produced and released into the extracellular milieu promotes cell proliferation and survival by acting on its G protein-coupled receptors and by transactivating a spectrum of receptor tyrosine kinases, including those of plateletderived growth factor (PDGF), transforming growth factor β, epidermal growth factor, hepatocyte growth factor, and VEGF. 41 Importantly, constitutive activation of SphK1 in endothelial cells induces a proinflammatory and proangiogenic phenotype, 42 and SphK inhibitors block pathologic neovascularization in animal models. 43 Given that many of the aforementioned growth factor receptors and pathogenic processes have been implicated in the pathogenesis of occlusive lesions in PAH, 44 we examined the effect of exogenous S1P on rat PAECs and found that it stimulated cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…These are characterized by having a lower content of n-3 polyunsaturated fatty acids (PUFA), and a higher content of n-6 PUFA. The fatty acids are incorporated into cellular membranes in a ratio corresponding to their dietary content (Henderson and Tocher 1987), where they serve many central homeostatic and immunologic functions (de Pablo and de Cienfuegos 2000;Vance 2008;Lebman and Spiegel 2008). A significant part of these processes are mediated through the action of eicosanoids including prostaglandins (PG) and prostacyclins.…”
Section: Introductionmentioning
confidence: 99%